Madura Coastal Potential as Ethnomathscience-Based Learning Content in Primary Schools - Pritasari, Ade Cyntia; Wulandari, Rika; Saptaningrum, Junia; Puspitasari, Aditya Dyah (International Research-Based Education Journal, 2023)
Utilization of the local cultural context in learning is one form of effort to optimize learning outcomes. Cultural context can be related to the content of lessons in schools such as mathematics (ethnomathematics) and science (ethnoscience). Ethnomathematics and ethnoscience, or what is later called ethnomathscience, is an approach to learning mathematics, physics, chemistry, and biology related to culture. Incorporating the potential of coastal tourism which is studied from an ethnomathscience point of view is very important in learning in order to prepare and shape the character of students who are always superior and ready to face the challenges of the times, but do not forget their ancestral heritage and are able to preserve both nature and culture. This study uses a mixed method that focuses on collecting, analyzing, and mixing qualitative and quantitative data in a single study. This research was conducted on the Madura Coast, especially in Pamekasan Regency. The research subjects were Pamekasan coastal communities, teachers, and students of Tanjung 3 Pamekasan Elementary School. The results of the study show that the Madura coast has the potential to be used as content in elementary school learning. Both teachers and students already understand the potential of the coast so that it can become the basis for contextual learning that promotes the culture of the local community. Mathematics and science content in elementary schools can be integrated with coastal culture.